2019
DOI: 10.1002/adfm.201906069
|View full text |Cite
|
Sign up to set email alerts
|

Template‐Assisted Synthesis of Metallic 1T′‐Sn0.3W0.7S2 Nanosheets for Hydrogen Evolution Reaction

Abstract: Crystal phase control still remains a challenge for the precise synthesis of 2D layered metal dichalcogenide (LMD) materials. The T′ phase structure has profound influences on enhancing electrical conductivity, increasing active sites, and improving intrinsic catalytic activity, which are urgently needed for enhancing hydrogen evolution reaction (HER) activity. Theoretical calculations suggest that metastable T′ phase 2D Sn 1−x W x S 2 alloys can be formed by combining W with 1T tin disulfide (SnS 2 ) as a tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
46
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 44 publications
5
46
0
Order By: Relevance
“…One explanation is that the Mo‐doping resulted in thinner petals and curly morphology, increasing the surface area of the catalyst. SnS 2 doping with W, which is isoelectronic to Mo, was reported to boost the electrochemical activity of SnS 2 by enhancing the metallic nature of SnS 2 due to the lattice distortion caused by the W incorporation, and by the formation of new catalytic sites: S atoms directly bonded to W and particularly those that are bonded with two W atoms . The Tafel slopes, calculated from the polarization curves, show significant decrease by doping (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…One explanation is that the Mo‐doping resulted in thinner petals and curly morphology, increasing the surface area of the catalyst. SnS 2 doping with W, which is isoelectronic to Mo, was reported to boost the electrochemical activity of SnS 2 by enhancing the metallic nature of SnS 2 due to the lattice distortion caused by the W incorporation, and by the formation of new catalytic sites: S atoms directly bonded to W and particularly those that are bonded with two W atoms . The Tafel slopes, calculated from the polarization curves, show significant decrease by doping (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…Hydrogen adsorption affinity is another crucial metric of electrocatalytic HER. [ 60–62 ] Generally, a moderate interaction is favorable since there is an intricate trade‐off between adsorption of hydrogen intermediate and desorption of hydrogen. [ 63 ] However, it is still challenging to achieve a hydrogen adsorption Gibbs free energy (Δ G H ) of 0 eV based on conventional strategies.…”
Section: Electric Field‐assisted Electrocatalytic Her/oermentioning
confidence: 99%
“…It has been reported that heteroatom doping can induce the transition of electrical transport behavior of 2D materials, from semiconducting to metallic for M-S heterostructure construction. [16,30] The electronic densities of states (DOS) of MoS 2 and Sn x Mo 1−x S 2 calculated with the density functional theory (DFT) method are shown in Figure 1. The projected DOS and electronic densities at the Fermi level for Sn x Mo 1−x S 2 confirmed that a slight Sn doping (≈2%) in MoS 2 could cause a transition from typical semiconductor to metal.…”
Section: Doi: 101002/advs202002172mentioning
confidence: 99%